2011
DOI: 10.1111/j.1582-4934.2009.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and functional properties of cardiomyocytes derived from human inducible pluripotent stem cells

Abstract: In view of the therapeutic potential of cardiomyocytes derived from induced pluripotent stem (iPS) cells (iPS-derived cardiomyocytes), in the present study we investigated in iPS-derived cardiomyocytes, the functional properties related to [Ca2+]i handling and contraction, the contribution of the sarcoplasmic reticulum (SR) Ca2+ release to contraction and the b-adrenergic inotropic responsiveness. The two iPS clones investigated here were generated through infection of human foreskin fibroblasts (HFF) with ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
110
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 31 publications
(71 reference statements)
14
110
1
Order By: Relevance
“…The cells were cultured with inactivated MEF as previously described. 20 HESCs and hiPSCs were passaged every 4-6 days using 1.5 mg/ml type IV collagenase (Worthington Biochemical Corporation, Lakewood, NJ, USA). We used previously defined criteria for characterization of hES and hiPS cells by examining their morphology, surface markers, growth rates, karyotype and pluripotency.…”
Section: Culturing Hesc and Hipsc Linesmentioning
confidence: 99%
“…The cells were cultured with inactivated MEF as previously described. 20 HESCs and hiPSCs were passaged every 4-6 days using 1.5 mg/ml type IV collagenase (Worthington Biochemical Corporation, Lakewood, NJ, USA). We used previously defined criteria for characterization of hES and hiPS cells by examining their morphology, surface markers, growth rates, karyotype and pluripotency.…”
Section: Culturing Hesc and Hipsc Linesmentioning
confidence: 99%
“…Cardiomyocytes derived by targeted differentiation from iPSC also exhibit the basic properties of cardiac muscle cells, namely: propensity for spontaneous rhythmic pulsation; expression of cardio-specific RNA and proteins and capacity for response to caffeine and ryanodine [71]. However, the same authors have reported that cardiomyocytes derived from iPSC exhibited negative force-frequency relationship and lower postrest potentiation than adult cardiac cells [71].…”
Section: Cardiomyocytes Derived By Differentiation Of Esc and Ipscmentioning
confidence: 88%
“…Diminished post-rest potentiation of the cardiac muscle is commonly seen in various cardiovascular conditions, including progressive heart hypertrophy and dilated cardiomyopathy; as well as in normal ageing. The responses to caffeine and ryanodine of iPSC-derived cardiomyocytes were also weaker than the response of adult cardiomyocytes [71]. Caffeine normally triggers an increase in cytosolic Ca 2+ whereas ryanodine decreases the levels of Ca 2+ , therefore, the maintenance of the balance of Ca 2+ levels in cardiomyocytes derived from pluripotent stem cells may not be identical to the balance in normal adult cardiomyocytes.…”
Section: Cardiomyocytes Derived By Differentiation Of Esc and Ipscmentioning
confidence: 89%
See 2 more Smart Citations